Effect of Raphanus Sativus (Radish) Leaf Extract on Atorvastatin Induced Hepatotoxicity in Rabbits - Obaid Anwar; Mazhar Iqbal; Sadia Chiragh; Owais bin Qadeer Gill; Muhammad Iqbal (Journal of Bahria University Medical and Dental College)
Objectives: To investigate hepato-protective effect of ethanolic leave extract of Raphanus sativus against atorvastatin induced hepatotoxicity in albino rabbits. Study design: Experimental study Material and Method: This study conducted at department of Physiology and Pharmacology, University of Agriculture, Faisalabad. The ethanolic extract of Raphanus sativus was prepared for hepatoprotective effect against hepatotoxicity produced by atorvastatin. Results: The results were compared with normal and experimental control. Serum was tested for ALT, AST, Alkaline Phosphatase and Bilirubin along with histological studies. Ethanolic extract of Raphanus sativus with 100mg/kg. of body weight dosage developed some changes representing hepatotoxicity but higher doses showed an increase in toxicity as observed on histologic sections. A reduction in fibrosis and cholestasis was observed which needs further evaluation. Conclusion: Ethanolic extract of raphanus sativus did not show any amelioration in the increased enzymes level however a reduction in cholestasis was observed as represented by decreases in alkaline phosphatase levels also confirmed by histological studies.